DNA Damage in Circulating Hematopoietic Progenitor Stem Cells as Promising Biological Sensor of Frailty. Issue 7 (9th February 2022) - Grasselli, Chiara; Bombelli, Silvia; Eriani, Stefano; Domenici, Giulia; Galluccio, Riccardo; Tropeano, Chiara; De Marco, Sofia; Bolognesi, Maddalena M; Torsello, Barbara; Bianchi, Cristina; Antolini, Laura; Rossi, Fabio; et al.
Abstract: Frailty is an age-related syndrome that exposes individuals to increased vulnerability. Although it is potentially reversible, in most cases it leads to negative outcomes, including mortality. The different methods proposed identify frailty after the onset of clinical manifestations. An early diagnosis might make it possible to manage the frailty progression better. The frailty pathophysiology is still unclear although mechanisms, in particular, those linked to inflammation and immunosenescence, have been investigated. A common feature of several clinical aspects involved in senescent organisms is the increase of oxidative stress, described as one of the major causes of deoxyribonucleic acid (DNA) damage accumulation in aged cells including the adult stem cell compartment. Likely, this accumulation is implicated in frailty status. The oxidative status of our frail, pre-frail, and non-frail population was characterized. In addition, the DNA damage in hematopoietic cells was evidenced by analyzing the peripheral blood mononuclear cell and their T lymphocyte, monocyte, circulating hematopoietic progenitor stem cell (cHPSC) subpopulations. The phosphorylation of C-terminal of histone H2AX at amino acid Ser 139 (γ-H2AX), which occurs at the DNA double-strand break focus, was evaluated. In our frail population, increased oxidative stress and a high level of DNA damage in cHPSC were found. This study may have potential implications because the increment of DNA damage in cHPSC could be suggestive of an organism impairment preceding the evident frailty. In addition, it may open the possibility for attenuation of frailty progression throughout specific drugs acting on preventing DNA damage or removing damaged cells